Natural variations in a barley aldehyde oxidase 1 gene affect seed germination and malting quality - Le Xu; Peng Wang; Xiaoqi Zhang; Qisen Zhang; Penghao Wang; Yanhao Xu; Chengdao Li; Wenying Zhang (Crop Journal)
Multiple phytohormones, including gibberellin (GA), abscisic acid (ABA), and indole-3-acetic acid (IAA), regulate seed germination. In this study, a barley aldehyde oxidase 1 (HvAO1) gene was identified, which is located near the SD2 (seed dormancy 2) region at the telomeric end of chromosome 5H. A doubled-haploid population (AC Metcalfe/Baudin) was used to characterize HvAO1 and validated its association with seed germination and malting quality. Aldehyde oxidase is predicted to catalyse the oxidation of various aldehydes, such as indoleacetaldehyde and abscisic aldehyde, into IAA and ABA, which is the final step of IAA/ABA biogenesis. This process influences the final IAA/ABA concentration in the seed, affecting the seed dormancy. Sequence analysis revealed substantial variations in the HvAO1 promoter regions between AC Metcalfe and Baudin. The combining seed germination tests, genetic variation analysis, gene expression, and phytohormone measurements showed that Baudin, which displays strong seed dormancy, has a specific sequence variation in the promoter region of the HvAO1 gene. This variation is associated with a higher expression level of the HvAO1 gene and an increased level of ABA than those in AC Metcalfe, which shows weak dormancy and lacks this sequence variation. In addition to its strong effect on the SD2 gene, HvAO1 shows excellent potential to fine-tune malting quality and seed dormancy, as evidenced by genotyping with HvAO1-specific markers, dormancy phenotypes, and malting quality. Our findings provide a new strategy for introducing favourable HvAO1 alleles to achieve the desired level of seed dormancy and high malting quality in barley.